2022
DOI: 10.1002/ptr.7546
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanism of oral baicalin treating psoriasis via suppressing Wnt signaling pathway and inhibiting Th17/IL‐17 axis by activating PPARγ

Abstract: Psoriasis (PSO), an immune‐mediated chronic inflammatory skin disease, has seriously affected the quality of patients' life. It is urgent to find effective medicines with lower costs and less side effects. Baicalin (HQG) is the main bioactive substance from Scutellaria baicalensis with effects of anti‐inflammation and immunoregulation. Herein, we explored the effect of oral HQG treating PSO and its potential mechanism. Firstly, network pharmacology was used to predict that HQG may act on Estrogen, TNF‐alpha (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…To identify the major targets of Ncs in alleviating skin immune cell infiltration and inflammation, we performed transcriptomic analysis of skin tissues from mice in the control group, Ncs group and IMQ group using RNA-seq ( Figure 4A ). Hierarchical clustering analysis of differentially expressed genes (DEGs) showed that compared with the control group, IMQ treatment up-regulated pathways related to keratinocyte differentiation and inflammation ( Figure S5 ), which was consistent with published studies ( 22 ). We further analyzed 558 DEGs (> 2-fold change) in the Ncs group versus the IMQ group and found that 230 were down-regulated due to Ncs treatment.…”
Section: Resultssupporting
confidence: 89%
“…To identify the major targets of Ncs in alleviating skin immune cell infiltration and inflammation, we performed transcriptomic analysis of skin tissues from mice in the control group, Ncs group and IMQ group using RNA-seq ( Figure 4A ). Hierarchical clustering analysis of differentially expressed genes (DEGs) showed that compared with the control group, IMQ treatment up-regulated pathways related to keratinocyte differentiation and inflammation ( Figure S5 ), which was consistent with published studies ( 22 ). We further analyzed 558 DEGs (> 2-fold change) in the Ncs group versus the IMQ group and found that 230 were down-regulated due to Ncs treatment.…”
Section: Resultssupporting
confidence: 89%
“…18 Studies demonstrated that baicalin (Bai) regulated immune-mediated chronic inflammatory signaling by targeting PPAR-γ. 19 In addition, Bai inhibited PDGF-BB-induced HSC activation and ameliorated LPS-induced HSCs migration in vitro. 20−22 Thus, Bai can be selected as an effective therapeutic agent against HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of HSCs is intricately linked with the TGF-β1/Smad signaling pathway, wherein reduction of TGF-β1-induced Smad2/3 phosphorylation impedes HSC activation. , The TGF-β1/Smad signaling pathway was regulated by peroxisome proliferator-activated receptor-gamma (PPAR-γ), which had protective effects on hepatic fibrosis . Studies demonstrated that baicalin (Bai) regulated immune-mediated chronic inflammatory signaling by targeting PPAR-γ . In addition, Bai inhibited PDGF-BB-induced HSC activation and ameliorated LPS-induced HSCs migration in vitro . Thus, Bai can be selected as an effective therapeutic agent against HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Baicalin ameliorates imiquimod (IMQ)induced skin damage, reduces in ammatory responses, and modulates immune disorders in mice. The underlying mechanism may be related to inhibition of the Wnt signaling pathway and inhibition of the Th17/IL-17 axis through activation of PPARγ [14]. However, the mechanism of action of baicalin on psoriasis requires further investigation.…”
Section: Introductionmentioning
confidence: 99%